2016
DOI: 10.1016/j.indcrop.2015.11.017
|View full text |Cite
|
Sign up to set email alerts
|

Chemometric analysis of French lavender and lavandin essential oils by near infrared spectroscopy

Abstract: International audienceChemometric treatments of near infrared (NIR) spectra were used firstly to understand data structure by principal component analysis (PCA), to discriminate, by partial least squares-discriminant analysis (PLS-DA) regression, French lavender and lavandin essential oils (EOs) samples (n = 160) and the seven varieties (Abrial, Fine, Grosso, Maillette, Matherone, Sumian and Super) and to quantify the main compounds such as linalyl acetate, linalool, eucalyptol and camphor by PLS regression mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
26
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(29 citation statements)
references
References 37 publications
3
26
0
Order By: Relevance
“…Lavender EOs are sometimes characterized by nonenantioselective techniques, such as gas chromatography [30] , vibrational spectroscopies [31,32] or both [33] . Their chiral components can be studied, on one hand, by enantioselective GC, that is available since the early 90s [34] , thanks to the enantioselectivity of cyclodextrin derivatives.…”
Section: Introductionmentioning
confidence: 99%
“…Lavender EOs are sometimes characterized by nonenantioselective techniques, such as gas chromatography [30] , vibrational spectroscopies [31,32] or both [33] . Their chiral components can be studied, on one hand, by enantioselective GC, that is available since the early 90s [34] , thanks to the enantioselectivity of cyclodextrin derivatives.…”
Section: Introductionmentioning
confidence: 99%
“…The unsupervised principal component analysis (PCA) was used to analyze the volatile components in lavender which were obtained at three harvest times in years 2012, 2015, and 2017. PCA is a method of compressing the dimension of vector data by extracting principal typical components from sample data set [2]. The PCA was preliminarily performed both on raw and pre-processed compound relative content of the whole dataset, to explore their characteristics and detect clustering or trends among samples.…”
Section: Multivariate Statistical Analysismentioning
confidence: 99%
“…In recent years, lavender is widely cultivated in Xinjiang of China. A number of studies have revealed that the lavender essential oil has a wide spectrum of biological activities such as sedative hypnosis [2] anti-depression, antibacterial [3], antioxidant [4], anti-coagulation, antimutation, and deworming ones [5,6]. Therefore, the essential oils of lavender plants are used in many applications such as in the food [7], cosmetic, fragrance, and pharmacy industries [8,9].…”
mentioning
confidence: 99%
“…In recent years, chromatographic profiling is often combined with multivariate analysis to evaluate the relationship between the chemical composition and quality, taxonomic identification or geographical origin [ 36 , 41 , 42 ]. Hyphenation of the chromatographic profile to multivariate analysis has already been performed in several studies for quality evaluation of EOs [ 43 , 44 , 45 , 46 ]. Since standards of primary pine EOs are still lacking and evaluation is challenging, verification of the chromatographic profile of these EOs combined with chemometric methods is needed.…”
Section: Introductionmentioning
confidence: 99%